Iowa Birdline update, January 23, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 23, 1989. Highlights include the sighting of all three Swan species in Iowa. Epson - sheet feed/flatbed